2017
DOI: 10.1016/j.canlet.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary ‘T4 immunotherapy’ of malignant mesothelioma using pan-ErbB re-targeted CAR T-cells

Abstract: Malignant mesothelioma remains an incurable cancer. We demonstrated that mesotheliomas expressed EGFR (79.2%), ErbB4 (49.0%) and HER2 (6.3%), but lacked ErbB3. At least one ErbB family member was expressed in 88% of tumors. To exploit ErbB dysregulation in this disease, patient T-cells were engineered by retroviral transduction to express a panErbB-targeted chimeric antigen receptor (CAR), co-expressed with a chimeric cytokine receptor that allows interleukin (IL)-4 mediated CAR T-cell proliferation. This comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…Analysis of a larger series of MPM that contained the subset presented here confirmed, as expected, that epithelioid tumors were associated with improved patient survival. 15 Expression of MET was detected by immunohistochemistry in 67.6% of MPM, either at low (28.1%), intermediate (24.6%) or high intensity (14.9%). Receptor distribution was cytoplasmic with membranous accentuation (Fig.…”
Section: Expression Of Met By Malignant Pleural Mesotheliomasmentioning
confidence: 94%
See 1 more Smart Citation
“…Analysis of a larger series of MPM that contained the subset presented here confirmed, as expected, that epithelioid tumors were associated with improved patient survival. 15 Expression of MET was detected by immunohistochemistry in 67.6% of MPM, either at low (28.1%), intermediate (24.6%) or high intensity (14.9%). Receptor distribution was cytoplasmic with membranous accentuation (Fig.…”
Section: Expression Of Met By Malignant Pleural Mesotheliomasmentioning
confidence: 94%
“…14 In keeping with this, we have recently demonstrated that ErbB re-targeted CAR T-cells achieve significant antitumor activity combined with excellent safety in pre-clinical models of malignant pleural mesothelioma (MPM). 15 The MET receptor tyrosine kinase is also aberrantly expressed in a large proportion of mesotheliomas [16][17][18][19][20][21] and has been proposed as an attractive therapeutic target in this disease. 18,22,23 Disappointingly however, a phase II trial of the selective MET inhibitor tivantinib has recently been terminated (https://clini caltrials.gov/ct2/show/NCT01861301; accessed March 25th, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These products are Major Histocompatibility Complex (MHC)-independent, meaning they can be utilised in diverse populations. Anti-mesothelin and anti-fibroblast activation protein (FAP; which is expressed ubiquitously in the MPM tumour microenvironment) CAR T-lymphocytes have both been shown to induce regression in MPM xenograft tumour models and can be delivered locally, to the pleura, using an indwelling pleural catheter [78,79]. Several Phase I studies testing the safety of these approaches are currently underway.…”
Section: Immunotherapymentioning
confidence: 99%
“…Amongst the CARs brought into the clinic (Table 1), the ligand-based CARs IL-13Rα and T1E are the ones with clinical information available [36, 46, 5759]. …”
Section: Natural Receptor- and Ligand-based Cars Tested In The Clinicmentioning
confidence: 99%